Mapping the Evolution and Thematic Trends of ChatGPT Use in Academic Writing: A Bibliometric Analysis - Anisa Kamaru; Jhems Richard Hasan; Nur Wahidah Thayib Pido (ITScience (Information Technology and Science), 2025)
Since its release in late 2022, ChatGPT has emerged as a notable phenomenon in academic writing and education, particularly within English language teaching. It has been widely adopted for drafting, editing, and evaluating academic texts. However, systematic mapping of its thematic evolution and development remains scarce. This study applies a bibliometric approach to examine the evolution and thematic trends of ChatGPT-related research in academic writing from 2022 to 2025. A total of 112 publications were retrieved from the Scopus database and analyzed using VOSviewer to identify publication growth patterns, author and institutional collaborations, and the emergence of new research themes. The analysis revealed a sharp increase in publications between 2023 (n = 46) and 2024 (n = 52), with dominant research themes focusing on benefits, ethical concerns, and pedagogical integration of ChatGPT. Emerging topics, including the evaluation of AI in academic assessment, demonstrated accelerated attention in 2024 and early 2025. Geographical distribution analysis showed concentration in countries such as the United States, China, and the United Kingdom, indicating unequal global access to technology and research resources. This study offers the first comprehensive bibliometric mapping of ChatGPT research in academic writing, highlighting its thematic development and research gaps. The findings provide a strategic foundation for advancing future studies, guiding educational practices, and informing policy decisions. The results are expected to support the ethical and effective integration of generative AI into writing instruction, particularly in English language teaching.